Extension of urban rail transit network and residential property values: a difference-in-differences approach - Diao, Mi; Leonard, Delon; Foo Sing, Tien (AESOP, 2016)
Urban rail transit has been widely considered an efficient and environmentally friendly mode of transport to address urban transport challenges. In the past decades, there is growing investment in urban rail transit systems in cities worldwide to meet the increasing demand for travel. According to urban economics theory, households make trade-offs between commuting cost and housing consumptions in selecting their residential locations, hence the accessibility benefit brought by urban rail transit could be capitalized into residential property values. On the empirical side, although a large body of studies have investigated the impact of transit station proximity on residential property values, most research rely on classical hedonic price analysis with cross-sectional data, thus unable to discern the causal effect of urban rail transit investment on residential property values. In this study, we revisit the relationship between urban rail transit and residential property values using the extension of Mass Rapid Transit (MRT) network in Singapore as an empirical setting. MRT is a heavy rail transit system, which forms the backbone of the public transport system in Singapore. To meet the increasing travel demand resulting from the steady economic growth and population growth, the Singapore Government has been continuously extending its MRT network in the past decades. Most notably, the Northeast Line (NEL) and the first two phases of the Circle Line (CCL) were opened in June 2003 and April 2010, respectively.
Proceedings of the IV World Planning Schools Congress, July 3-8th, 2016 : Global crisis, planning and challenges to spatial justice in the north and in the south